PECULIARITIES OF THE INFLUENCE OF PUSH-SYNDROME ON THE REHABILITATION PROCESS OF PATIENTS WITH ACUTE CEREBRAL CIRCULATION DISORDERS - Sabadosh, M.; Yastremska, S.; Kormiltsev, V.; Dub, M. (Rehabilitation and Recreation, 2022)
Stroke in Ukraine, as in the other part of the world, remains one of the most common causes of disability and premature death. Brain damage due as the acute cerebrovascular accident is the cause of various disorders, including motor, sensory, cognitive and emotional. All these disorders and pathological syndromes are aggravating and slowing down factors in the process of restoring lost functions. Goal. To study the use of physical therapy as a therapeutic method aimed at regressing PUSH syndrome in patients after stroke in the acute period. Methods. Analysis of scientific literature and clinical experience of foreign research. Results. There is low data about the ability of patients with PUSH syndrome to resume daily activities. Individual works concern the peculiarities of training depending on the initial functional parameters of such patients. Forced vertical control during locomotion, as well as Lokomat therapy, are recognized as effective methods of reducing the PB of patients with stroke and have a significant impact on balance. Visual feedback computer interactive training has been more effective in recovering from PUSH than mirrored visual feedback training. And training active side sitting can help improve posture orientation in patients with RV. And although the effectiveness of physical therapy in patients after stroke is unequivocally recognized, among the studies we did not find those that study the specifics of the use of balance therapy and its impact on reducing the manifestations of PB. Conclusions. Approaches to deviations in the perception of verticality in people with Pusher Behavior (PB) and the impact of these disorders on the quality and duration of rehabilitation were retrospectively analyzed. The presence of PUSH syndrome in a patient should not be an obstacle to training standing, balance and gait, although it will obviously have its own characteristics. Moreover, by increasing the flow of sensorimotor afferent signals during exercise, PB regression may be accelerated.